2017
DOI: 10.3389/fpls.2017.00745
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Identification and Expression Pattern of the Vicinal Oxygen Chelate Family in Rapeseed (Brassica napus L.)

Abstract: Vicinal oxygen chelate proteins (VOC) are members of the metalloenzyme superfamily, which plays roles in many biological reactions. Some members of the VOC superfamily have been systematically characterized but not in Brassica napus. In this study, 38 VOC genes were identified based on their conserved domains. The present results revealed that most of the BnaVOC genes have few introns, and all contained the typical VOC structure of βαβββ modules. The BnaVOC genes are distributed unevenly across 15 chromosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
(107 reference statements)
2
21
0
Order By: Relevance
“…Altogether, whole genome triplication followed by main segmental duplication, played a major role in the expansion of BnHsp70 gene family (Cheng, Wu & Wang, 2014; Chalhoub et al, 2014; Liu et al, 2014). Similar genome duplication patterns have been observed in late embryogenesis abundant ( LEA ) genes and Vicinal Oxygen Chelate ( VOC ) genes of Brassica species (Liang et al, 2016; Liang et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Altogether, whole genome triplication followed by main segmental duplication, played a major role in the expansion of BnHsp70 gene family (Cheng, Wu & Wang, 2014; Chalhoub et al, 2014; Liu et al, 2014). Similar genome duplication patterns have been observed in late embryogenesis abundant ( LEA ) genes and Vicinal Oxygen Chelate ( VOC ) genes of Brassica species (Liang et al, 2016; Liang et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
“…While polyploidy is a vital mechanism of gene family expansion, tandem duplication and infrequently segmental duplication are thought to commonly evaluated mechanisms for gene family copy numbers evolution and expansion (Liang et al, 2017). Therefore, it was assessed that roles of gene duplication events and Darwin’s positive selection in the divergence of genes for understanding Hsp70 gene family expansion (Cannon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some other gene superfamilies in the allotetraploid species B . napus have been described, including the SnRK2 , ERF , VOC , ACBP , and MAPKKK superfamilies [ 52 , 53 , 54 , 55 , 56 ]. In the current study, we found that the copy number of bZIP genes varied from two to eight, which is consistent with the finding that two or more copies of homologous genes have been detected in B .…”
Section: Discussionmentioning
confidence: 99%
“…, , , , , , , ), respectively. These copies were selected because their expression levels were relatively stable and higher in seeds and leaves during drought, based on our previous studies (Liang et al ., , ). In addition, they were located in four different A or C subgenomes of B. napus .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, it was revealed that the LEA and VOC proteins were highly expressed in B. napus plants that had high oil content (Gan et al ., ). We also found that most of the BnLEA and BnVOC genes had higher expression levels under drought stress in B. napus with high oil content (Liang et al ., , ). These results suggested that drought‐stress‐responsive genes might have a relationship with lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%